Soil microbial community structure and activity in monospecific and mixed forest stands, under Mediterranean humid conditions (Plant and Soil, 2011)
Aims We investigated the link between tree community composition and soil microbial community biomass and structure in central-eastern Spain. Methods The effects of the forest stand composition on the soil organic matter dynamics and on the structure and activity of the soil microbial community have been determined using phospholipid fatty acid profiles and soil enzymatic activities. Results The soil and litter N and C contents were higher in Pinus nigra Arn. ssp. salzmannii and Quercus ilex mixed forest stands (SBHO) and in long-term unmanaged Pinus nigra Arn. ssp. salzmannii forest stands (SBPC) than in pure Pinus nigra Arn. ssp. salzmannii forest stands (SBPA) and Pinus nigra Arn. ssp. salzmannii and Juniperus thurifera mixed forest stands (SBSJ). The bacterial biomass was significantly higher in SBSJ and SBPA than in SBPC and SBHO. The results show an uncoupling of the soil microbial biomass and its activity. pH is related to microbial biomass and its community structure under a Mediterranean humid climate. Conclusions The tree species seem to affect the biomass of the soil microbial community and its structure. The pH, but not the C/N ratio, is a factor influencing the microbial dynamics, biomass, and community structure.

Soil microbial activity as a biomarker of degradation and remediation processes - Pascual, J. a; Garcia, C.; Hernandez, T.; Moreno, J. L.; Ros, M. (Soil Biology and Biochemistry, 2000)
Several organic matter fractions together with biological and biochemical parameters were measured in a range of intensively farmed soils in SE Spanish Mediterranean region, which had been abandoned (i.e. not used in agriculture) for different periods of time. These soils were compared with adjacent natural soils that had never been used for agriculture. There was a general decline of total organic carbon (TOC), extractable humic substances, water-soluble carbon (WSC) and carbohydrates, microbial biomass and respiration with the time elapsed since abandonment. There was also a decline in plant cover in the abandoned soils. When a degraded soil was amended with municipal solid waste at rates of 6.5 and 26 kg m 22 as a potential means of remediation, TOC, humic substances, WSC, microbial biomass and respiration rates signi®cantly increased but only at the higher rate of amendment. Plant cover was signi®cantly enhanced by both rates of the amendments and was still present 10 years after the amendment. These data con®rm that agricultural soil abandonment leads to soil degradation and that the addition of urban waste could be a suitable technique with which to restore their quality
Keywords: dehydrogenase; hydrolases; organic matter; soil remediation